2019
DOI: 10.5039/agraria.v14i3a6559
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e colonização micorrízica do tomateiro IPA06 inoculado com fungos micorrízicos arbusculares em substrato orgânico

Abstract: RESUMO: O tomateiro IPA06 é uma variedade que apresenta frutos resistentes ao transporte e adaptada ao cultivo rústico, cuja interação com fungos micorrízicos arbusculares (FMA) ainda não foi encontrada na literatura. O objetivo deste trabalho foi avaliar o crescimento e a colonização do tomateiro IPA06 cultivado com FMA em substrato orgânico. O delineamento experimental utilizado foi inteiramente casualizado composto pelo cultivo do tomateiro IPA06 em cinco tratamentos (controlesem inóculo fúngico e quatro in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
(44 reference statements)
0
1
0
4
Order By: Relevance
“…However, it is important to emphasize that the mycorrhizal colonization rate may not be directly correlated to plant growth (Chaiyasen et al, 2017), as observed in the present study. Mendonça et al (2019) have used fungal species Gigaspora albida, R. clarum, C. etunicatum, and Acaulospora morrowiae in tomato plants and observed colonization rate ranging from 40.3% to 83.8% during plant growth, 42 days after inoculation. However, the growth of plants presenting mycorrhizal colonization was not affected by it in comparison to the control.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to emphasize that the mycorrhizal colonization rate may not be directly correlated to plant growth (Chaiyasen et al, 2017), as observed in the present study. Mendonça et al (2019) have used fungal species Gigaspora albida, R. clarum, C. etunicatum, and Acaulospora morrowiae in tomato plants and observed colonization rate ranging from 40.3% to 83.8% during plant growth, 42 days after inoculation. However, the growth of plants presenting mycorrhizal colonization was not affected by it in comparison to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto o aumento do período de cultivo favoreceu o incremento significativo da altura da planta, cujos dados foram ajustados à regressão linear em todos os tratamentos (Tabela 1, Figura 1). Nestes resultados deve-se considerar que a eficiência dos isolados micorrízicos no desenvolvimento das plantas do tomateiro depende da interação com a cultivar em específico (BANLA et al, 2015;MENDONÇA et. al., 2019b, WANG et.…”
Section: Crescimento Das Mudas Do Tomateiro Ipa06 Com Isolados Micorr...unclassified
“…O tomateiro (Solanum lycopersicum L.) é uma solanácea capaz de estabelecer uma relação simbiótica com FMA, onde a ação positiva no crescimento vegetativo e na produção depende da interação da espécie micorrízica com a cultivar do tomateiro (BANLA et al, 2015;MENDONÇA et. al., 2019b, WANG et.…”
Section: Introductionunclassified
See 2 more Smart Citations